2017
DOI: 10.3390/cancers9060054
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miRNA Expression in Cancer Associated Fibroblasts (CAFs) and Its Consequences on the Tumor Microenvironment

Abstract: The tumor microenvironment, including cancer-associated fibroblasts (CAF), has developed as an important target for understanding tumor progression, clinical prognosis and treatment responses of cancer. Cancer cells appear to transform normal fibroblasts (NF) into CAFs involving direct cell-cell communication and epigenetic regulations. This review summarizes the current understanding on miR involvement in cancer cell—tumor environment/stroma communication, transformation of NFs into CAFs, their involved targe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 74 publications
1
61
0
1
Order By: Relevance
“…A role for microRNA (miRNA) in the epigenetic regulation of fibroblasts has also been reported, with distinct miRNAs activating fibroblasts in different organs . miRNAs also play a role in regulating EMT, EndMT, and macrophage‐to‐mesenchymal transition .…”
Section: Epigenetic Control Of Fibroblast Identitymentioning
confidence: 99%
“…A role for microRNA (miRNA) in the epigenetic regulation of fibroblasts has also been reported, with distinct miRNAs activating fibroblasts in different organs . miRNAs also play a role in regulating EMT, EndMT, and macrophage‐to‐mesenchymal transition .…”
Section: Epigenetic Control Of Fibroblast Identitymentioning
confidence: 99%
“…The tumor-promoting ability of CAFs is enhanced by microRNA dysregulation [254]. CAFs stimulate EMT in gastric cancer cells in a microRNA-214-dependent manner-it induces tumor-promoting ability of CAFs through fibroblast growth factor 9 (FGF9) targeting [255,256].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…It has long been known that small molecules, cytokines, and growth factors mediate functional interactions between cancer cells and the tumor microenvironment (Schoepp et al, 2017). However, recent studies have revealed that cancer cells also transfer functional information at the paracrine level using EVs.…”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%